The Cost of Doing Business in Africa : Evidence from the World Bank’s Investment Climate Data - World Bank (Washington, DC, 2012)
This paper looks at firm-level evidence on the African business environment from surveys undertaken for Investment Climate Assessments by the World Bank in 2000-2004. These surveys confirm a pattern of generally low "factory-floor" productivity, and show that this is partly due to business environment-related losses. The surveys also show the importance of high indirect costs in further depressing the "net" productivity of African firms relative to those in other regions. Reforms are moving forward but more slowly than is needed to accelerate growth; this raises the possibility that countries settle into a low-level political equilibrium sustained partly by structural and ethnic cleavages.